1981
DOI: 10.1136/jcp.34.4.386
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal mucosal morphometry in children with and without gut symptoms and in normal adults.

Abstract: SUMMARY Nineteen diagnostic peroral biopsy specimens from 18 children without diarrhoea, vomiting, or abdominal pain ('control' children) were compared with those taken from 23 children with diarrhoea of varying aetiology to establish the morphometric characteristics ofjejunal mucosa in childhood. Comparison was also made with normal jejunal mucosa from adults. Statistical analysis of each characteristic individually showed no significant difference between the 'control' children and those with diarrhoea, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
5

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
2
21
1
5
Order By: Relevance
“…25 não detectaram diferença entre os grupos. No entanto, a comparação entre 24 com histologia "normal" e 18 com atrofia vilosa parcial (34,1 ± 3,4 µm e 28,9 ± 4,7 µm, respectivamente) mostrou diferença estatisticamente significante entre os grupos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…25 não detectaram diferença entre os grupos. No entanto, a comparação entre 24 com histologia "normal" e 18 com atrofia vilosa parcial (34,1 ± 3,4 µm e 28,9 ± 4,7 µm, respectivamente) mostrou diferença estatisticamente significante entre os grupos.…”
Section: Discussionunclassified
“…25 naqueles com atrofia vilosa parcial, bem como àqueles detectados por Wood e colaboradores 26 que, ao avaliarem pacientes adultos, observaram diferença estatisticamente significante entre pacientes brancos ingleses (30,2 µm) e imigrantes indianos (28,3 ± 2,7 µm) e afro-caribenhos (27,2 ± 2,7 µm). Estes autores propõem que tais achados "...refletem a morfologia 'normal' de pacientes imigrantes, determinada por fatores ambientais".…”
Section: Discussionunclassified
“…[Previous work (29) has shown that partial villous atrophy occurs frequently in children, even those with no gastrointestinal symptoms.] But the presence of ACC did not correlate with histologic abnormality either in the patient group or in the control group, and neither did it correlate with the IgA plasma cell count (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They were divided into at least two portions, which were fixed immediately, one for routine histology and one for immunofluorescence (15). Assessment of the villous morphology, normal or partial villous atrophy, was made as previously described (29).…”
Section: Methodsmentioning
confidence: 99%
“…Histological analysis was performed according to the criteria proposed by others (8)(9)(10), with small modifications. The material was scored as follows: grade 0 or normal: high and thin villi are present throughout the extension of the fragment examined and correspond to 2.5 to 3 times the depth of the crypts.…”
Section: Methodsmentioning
confidence: 99%